A comparison of Australian bean yellow mosaic virus isolates using molecular hybridisation analysis - Abu Samah, Norani; Randles, J. W. (Wiley-Blackwell Publishing, 1983)
Twenty-nine isolates of bean yellow mosaic virus (BYMV), obtained over 5 yr by sampling of a limited area in south-eastern South Australia and western Victoria (Collection I), resembled each other in host range and symptomatology. Three reference isolates and nine other isolates (Collection E) from across southern Australia differed in host range and symptomatology from each other, and from the members of collection I.